2018
DOI: 10.1002/oby.22274
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Reduces Skeletal Muscle Work Efficiency in Weight‐Reduced and Non–Weight‐Reduced Subjects

Abstract: Objective: To determine whether resistance training is similarly effective in reducing skeletal muscle efficiency and increasing strength in weight-reduced and maximal weight subjects. Methods: We examined the effects of supervised resistance exercise on skeletal muscle in 14 overweight and obese individuals sustaining a 10% or greater weight loss for over 6 months, and a phenotypically similar group of 15 subjects who were nonweight-reduced and weight stable at their maximal lifetime body weight. We assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Would different energy flux targets and/or exercise approaches be warranted based on the magnitude of behavioral adaptations (decline in PAEE due to decreased NEAT and/or ExEE) versus contributions to the energy gap of AT? These questions appear largely unanswered at this time, but it would seem that regardless of the etiology of the lower TDEE following weight loss, regular exercise to increase energy flux could decrease the probability of weight gain by some or all of the following depending on the individual: increasing PAEE [10], increasing REE and offsetting AT to some extent [10], enhancing appetite regulation [28], increasing or preserving FFM and minimizing collateral fattening [91], and offsetting skeletal muscle AT as recently reported by Rosenbaum et al [92]. They found that resistance exercise training significantly attenuated the increase in skeletal muscle work efficiency that accompanied weight loss.…”
Section: Is Energy Flux Important For Weight Loss Maintenance and mentioning
confidence: 98%
“…Would different energy flux targets and/or exercise approaches be warranted based on the magnitude of behavioral adaptations (decline in PAEE due to decreased NEAT and/or ExEE) versus contributions to the energy gap of AT? These questions appear largely unanswered at this time, but it would seem that regardless of the etiology of the lower TDEE following weight loss, regular exercise to increase energy flux could decrease the probability of weight gain by some or all of the following depending on the individual: increasing PAEE [10], increasing REE and offsetting AT to some extent [10], enhancing appetite regulation [28], increasing or preserving FFM and minimizing collateral fattening [91], and offsetting skeletal muscle AT as recently reported by Rosenbaum et al [92]. They found that resistance exercise training significantly attenuated the increase in skeletal muscle work efficiency that accompanied weight loss.…”
Section: Is Energy Flux Important For Weight Loss Maintenance and mentioning
confidence: 98%
“…Response to exogenous leptin is also dependent on energy stores and balance. When leptin concentrations are raised above an individual "threshold" (which is higher in individuals with obesity), the relevant neuronal tracts are less sensitive (LeDuc and Leibel, 2019;Zhao et al, 2019) and further leptin administration evokes little if any response in humans (Rosenbaum et al, 2018b).…”
Section: Leptin Signaling Is Non-linearmentioning
confidence: 99%
“…In their seminal studies, Rosenbaum, Leibel et al reported that metabolic slowing after CR mostly affects nonresting energy expenditure (NREE) with less impact on resting energy expenditure (REE) 6 . They further showed that metabolic slowing after weight loss is partly mediated by increased skeletal muscle work efficiency 9 , 10 , which can be reversed by leptin and triiodothyronine supplementation as well as resistance training 44 , 45 . These previous results indicate that increased energy efficiency in skeletal muscle work following weight loss may predispose to weight regain which appears contradictory to our present findings showing “decreased” energy efficiency during eucaloric conditions at baseline predicts weight regain.…”
Section: Discussionmentioning
confidence: 99%